When Less is better: Messages that Present Dietary Carbon Emissions Data at the individual (vs. Aggregate) Level Increase Commitment to Sustainable Beef Consumption. (1st July 2022) - Aberman, Youval; Plaks, Jason
Abstract: The environmental footprint embedded in the human diet is massive. To convey the enormity of the problem, persuasive environmental messages often report large-scale, aggregate data (such as the billions of tons of greenhouse gases released to the atmosphere annually by the beef industry.) Is this strategy effective? In five studies (total N = 1237), the environmental footprint of beef was presented to participants with either aggregate, nation-level numeric data, or with the same data scaled to the individual level. Across the studies, a clear pattern emerged: Participants who received aggregate-level (versus individual-level) data perceived less of a connection between their behavior and the environment and expressed less intention to curb their meat consumption. These data suggest that aggregate environmental figures, rather than raising urgency, may instead demotivate many message recipients.